The features and factors in the acquisition of English existential constructions at the syntax–pragmatics interface by Chinese learners - Jiang, Shan; Zhang, Huiping (Frontiers in Psychology, 2022)
This study adopted a mixed-method study design to investigate the acquisitional features of English existential constructions at the syntax-pragmatics interface by Chinese learners, and explore the factors for non-native performance from the perspective of the Interface Hypothesis. A questionnaire was administered online to 300 Chinese learners of English and 20 English natives at a University in China, which included a picture description test and a context-matching test. Follow-up interviews were conducted with 30 Chinese learners. The experimental data were conducted using comparing means and generalized linear mixed model. Results showed that Chinese learners overproduced existential constructions and reached a native-like level until the advanced stage. Moreover, Chinese learners displayed different preference patterns for existential constructions from English natives, and basically reached a native-like level by the intermediate stage. The qualitative data provided possible explanations for non-native performance. The analysis revealed that non-native performance in production attributed to L1 negative transfer and input frequency, while that in comprehension resulted from underspecification of form-function mapping, input frequency and contexts. Based on the findings, some implications on syntax-pragmatics teaching and L2 interface studies are provided.